Antimicrobial role of Lactobacillus species as potential probiotics against enteropathogenic bacteria in chickens - Ahmed, Zulfiqar; Vohra, Muhammad Sufyan; Khan, Muhammad Noman; Ahmed, Ayaz; Khan, Taseer Ahmed (The Journal of Infection in Developing Countries, 2019)
Introduction: The emergence of antimicrobial resistance among bacterial community resulted in a ban on drugs as the growth promoter in poultry feed. This situation demands to explore alternatives as food supplements with health benefit to poultry. Therefore, probiotic microorganisms, which are considered as safe and possess various health benefits can be a choice. Present study was designed to explore the probiotic potential of the isolated lactobacillus species in chickens. Methodology: Out of 220 samples, 100 Lactobacillus species were isolated from various regions of chicken intestine. They were further characterized on the basis of morphology, staining and catalase test. Species-level identification was made by amplifying Lactobacillus specific 16S rRNA gene. Out of 100 isolates, 21 were selected for sequencing on the basis of band intensity. Results: Among 21 sequences, 16 were identified as L. paracasei (n = 6), L. salivarius (n = 3), L. johnsonii (n = 3), and L. agilis, L. fermentum, L. sakei, and L. curvatus (n = 1 each). These strains were found to be significantly acid-tolerant with 81.68 - 85.01% survival rate at pH 2)and bile-tolerant with 81.96 -84.65% survival rate at 0.3% bile. Except three; all strains showed salt tolerance to 2% and 4% NaCl. Among 21 Lactobacillus strains, 6 showed good antimicrobial activities against S. aureus, Salmonella Typhimurium and E. coli. Conclusion: Lactobacillus species with probiotic property can be used in poultry feed formulation for their health benefit to combat gastrointestinal infections.